2019
DOI: 10.1186/s12711-019-0450-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heterozygosity on performance of purebred and crossbred pigs

Abstract: Background In pigs, crossbreeding aims at exploiting heterosis, but heterosis is difficult to quantify. Heterozygosity at genetic markers is easier to measure and could potentially be used as an indicator of heterosis. The objective of this study was to investigate the effect of heterozygosity on various maternal and production traits in purebred and crossbred pigs. The proportion of heterozygosity at genetic markers across the genome for each individual was included in the prediction model as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 29 publications
2
30
1
8
Order By: Relevance
“…Although the genetic basis of heterosis is still a subject of investigation, its effect is difficult to quantify. Thus, heterozygosity, which represents the proportion of heterozygote genotypes in the population, may be a useful indicator and has been often used to evaluate the degree of heterosis (Akanno et al, 2018;Iversen et al, 2019;Prastowo et al, 2021). According to Queiroz et al (2013), heterozygosity has a significant effect on performance traits in Brangus animals and its inclusion in the model may improve prediction accuracy (Raidan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although the genetic basis of heterosis is still a subject of investigation, its effect is difficult to quantify. Thus, heterozygosity, which represents the proportion of heterozygote genotypes in the population, may be a useful indicator and has been often used to evaluate the degree of heterosis (Akanno et al, 2018;Iversen et al, 2019;Prastowo et al, 2021). According to Queiroz et al (2013), heterozygosity has a significant effect on performance traits in Brangus animals and its inclusion in the model may improve prediction accuracy (Raidan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The pooled indigenous animals had an average heterozygosity of 0.238 (SD = 0.023), consistent with the extra heterozygosity expected in admixtures between the African B. taurus and Bos indicus ancestral populations. Including heterozygosity proportion in the model for genetic evaluation increases the prediction accuracy of traits and it also has the potential to be used in mate selection in order to maximize heterozygosity in the offspring ( De Cara et al, 2011 ; Iversen et al, 2019 ). A previous study by Mbole-Kariuki et al (2014) using a medium-density (50k SNPs) dataset reported a lower average heterozygosity level for N’Dama 0.17 (SD = 0.08) than the pooled African B. taurus , and a higher average heterozygosity level for Sheko 0.26 (SD = 0.003) compared to the pooled indigenous animals in our study.…”
Section: Resultsmentioning
confidence: 99%
“…, piglet) per 10% increase in genomic inbreeding) in P1, P2 and CB , and were distributed across all QTL. As reference, estimates of inbreeding depression reported in the literature for litter size ranged from -2 to -9 piglets per 100% of observed homozygosity ( Xiang et al 2016 ; Iversen et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Xiang et al's model also includes a regression on "genomic inbreeding" (observed homozygosity) in PB and CB animals to measure individual "inbreeding depression". This can be seen as the opposite of heterosis and therefore it is possible to correct by, and to predict, individual heterosis (Iversen et al 2019). In this manner, all essential aspects of the joint PB -CB prediction are considered in a single analysis.…”
mentioning
confidence: 99%